Hubungan Kebiasaan Merokok dengan Pola Tidur dan Kejadian Hipertensi pada Tahanan di Ruang Tahanan Direktorat Tahanan dan Barang Bukti Polda Kalimantan Tengah - Eka Cahaya; Meilitha Carolina; Eva Priskila (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Smoking is the activity of inhaling or drawing in cigarette smoke using a pipe or cigarette. Smoking habits can affect sleep patterns and blood pressure. Cigarettes contain chemicals that stimulate the brain to release adrenaline, which can increase blood pressure and brain activity, making it difficult to fall asleep due to the stimulant effects of nicotine. Cigarettes that enter the bloodstream can damage blood vessel linings, leading to arteriosclerosis and high blood pressure. This study aims to examine the relationship between smoking habits, sleep patterns, and the incidence of hypertension among detainees at the Directorate of Detainees and Evidence Police Department of Central Kalimantan. Method: A correlational study with a cross-sectional approach, with a population of 46 detainees and a total sampling method involving 46 respondents. Data were collected using questionnaires. Data analysis was performed using Spearman Rank and Chi-square tests. Results: Statistical testing showed a significance value (2-tailed) of 0.00 < 0.05, indicating a relationship between smoking habits and sleep patterns. However, the p-value was 0.833 > 0.05, demonstrating no relationship between smoking habits and hypertension incidence among detainees at the Directorate of Detainees and Evidence Police Department of Central Kalimantan. Conclusion: The majority of respondents had moderate smoking habits, with 25 individuals (54.3%), and a smaller group had heavy smoking habits, with 10 individuals (21.7%). Most respondents had a good sleep pattern, with 32 individuals (69.6%), while a smaller group had poor sleep patterns, with 5 individuals (10.9%). The majority of respondents did not have hypertension, with 25 individuals (52.2%), and a smaller group had hypertension, with 22 individuals (47.8%).